Loyalty Survey Based on Net Promoter Score in A Tertiary Hospital in Indonesia - Cita RS Prakoeswa; Nur Hidayah; Arlina Dewi; Faradillah Mutiani; Agus Aan Adriansyah; Amak M. Yaqub (Faculty of Medicine Universitas Indonesia, 2022)
The COVID-19 pandemic has further emphasized the importance of comprehensive health care management. Currently, hospital services are a concern for many parties. With this study, we aim to measure loyalty in hospital care. Loyalty measurements carried out systematically and continuously can be expected to improve the quality and ultimately increase the profitability of hospitals as health services. This study is descriptive retrospective study from loyalty measurement using net promoter score (NPS) in a periodic survey of a tertiary hospital in the east part of Indonesia in 2021. Respondents were patients and their families based on purposive sample. After the respondents were categorized as promoter, passive, and detractor, the answers to qualitative questions included reasons for certain assessments marked as NPS 2 and what should the hospital do to improve the assessments marked as NPS 3. The respondents (2,488) were categorized as promoters, 1,570 respondents were categorized as passive, and 99 respondents were categorized as detractors. Overall NPS in 2021 is 57.5%. The most frequent answer for NPS 2 in all quarters and all groups were excellent and satisfactory hospital services. Evaluation of NPS 3 shows that all groups mostly recommend improving and maintaining hospital services. The high NPS results indicate the loyalty of the respondents to the hospital. Despite hospital services being considered excellent, several parts need to be improved. Specific recommendations from respondents are needed to improve hospital services. Keywords: loyalty, net promoter score, hospital service, customer satisfaction, service quality. Survey Loyalitas Berdasarkan Net Promoter Score di Salah Satu Rumah Sakit Tersier di Indonesia Abstrak Pandemi COVID-19 semakin menegaskan pentingnya manajemen pelayanan kesehatan yang komprehensif. Saat ini, pelayanan rumah sakit menjadi perhatian banyak pihak. Dengan penelitian ini, kami bertujuan untuk mengukur loyalitas di rumah sakit. Pengukuran loyalitas secara sistematis dan berkesinambungan diharapkan dapat meningkatkan kualitas dan profitabilitas rumah sakit sebagai pelayanan kesehatan. Penelitian deskriptif retrospektif ini mengukur loyalitas menggunakan net promoter score (NPS) pada survei berkala sebuah rumah sakit tersier di Indonesia bagian timur pada tahun 2021. Responden adalah pasien dan keluarga pasien yang berkunjung ke rumah sakit berdasarkan pengambilan sampel yang disengaja. Setelah responden dikategorisasikan menjadi promoter, pasif, dan pencela, jawaban atas pertanyaan kualitatif menyertakan alasan responden memberikan penilaian tertentu ditandai sebagai NPS 2 dan apa yang harus dilakukan rumah sakit untuk meningkatkan penilaian ditandai sebagai NPS 3. Hasil: 2488 responden tergolong promotor, 1570 responden tergolong pasif, dan 99 responden tergolong pencela. Secara keseluruhan NPS pada tahun 2021 adalah 57,5%. Jawaban paling sering dari NPS 2 di semua triwulan dan semua kelompok adalah pelayanan rumah sakit yang baik dan memuaskan. Evaluasi NPS 3 menunjukkan bahwa semua kelompok sebagian besar memberikan rekomendasi berupa peningkatan dan mempertahankan pelayanan rumah sakit. Hasil NPS yang tinggi menunjukkan loyalitas responden terhadap pelayanan yang diberikan rumah sakit. Walaupun pelayanan rumah sakit sudah dianggap baik, namun ada beberapa bagian yang perlu diperbaiki. Diperlukan rekomendasi khusus dari responden untuk meningkatkan pelayanan rumah sakit. Kata kunci: loyalty, net promoter score, hospital service, customer satisfaction, service quality.